In vitro antifungal effect and inhibitory activity on biofilm formation of seven commercial mouthwashes. (21st May 2014) - Fu, J; Wei, P; Zhao, C; He, C; Yan, Z; Hua, H
<x xml:space="preserve">Abstract</x> Objective To investigate the antifungal ability of seven over‐the‐counter mouthwashes against planktonic and sessile Candida albicans and Candida krusei. Materials and Methods The seven mouthwashes studied were Listerine®, compound chlorhexidine solution, povidone iodine solution (PV‐I), cetylpyridinium chloride solution, Colgate® Plax, Crest® Prohealth Mouthwash, and NaHCO3. The antifungal ability of each mouthwash against ATCC90028, ATCC6258, and 10 clinical C. albicans isolates was tested using disk diffusion tests, the broth microdilution method, and biofilm testing with two different XTT‐reduction assays. Fluconazole was used as a positive control, and the experiments were performed in triplicate. Results Chlorhexidine and cetylpyridinium chloride had the largest inhibition zones for ATCC90028 and ATCC6258 (18.6 ± 3.5 and 19 ± 1.6 mm, respectively). Cetylpyridinium chloride was the most effective at inhibiting all of the planktonic C. albicans strains and ATCC6258 with the minimum inhibitory concentration (MIC). As the maturity of the biofilms increased, the change in sessile cell MIC of the mouthwashes was much smaller than that of fluconazole. For the mature biofilms, chlorhexidine, PV‐I, and cetylpyridinium chloride produced the greatest reductions in metabolism (60–80%). Conclusion Most of these seven mouthwashes had significant antifungal activity for both planktonic and sessile Candida species.